Trends from 2002 to 2010 in Daily Breakfast Consumption and its Socio-Demographic Correlates in Adolescents across 31 Countries Participating in the HBSC Study. - Giacomo Lazzeri; Namanjeet Ahluwalia; Birgit Niclasen; Andrea Pammolli; Carine Vereecken; Mette Rasmussen; Trine Pagh Pedersen; Colette Kelly (PLoS ONE, 2016)
Breakfast is often considered the most important meal of the day and children and adolescents can benefit from breakfast consumption in several ways. The purpose of the present study was to describe trends in daily breakfast consumption (DBC) among adolescents across 31 countries participating in the HBSC survey between 2002 to 2010 and to identify socio-demographic (gender, family affluence and family structure) correlates of DBC. Cross-sectional surveys including nationally representative samples of 11-15 year olds (n = 455,391). Multilevel logistic regression analyses modeled DBC over time after adjusting for family affluence, family structure and year of survey. In all countries, children in two-parent families were more likely to report DBC compared to single parent families. In most countries (n = 19), DBC was associated with family affluence. Six countries showed an increase in DBC (Canada, Netherland, Macedonia, Scotland, Wales, England) from 2002. A significant decrease in DBC from 2002 was found in 11 countries (Belgium Fr, France, Germany, Croatia, Spain, Poland, Russian Federation, Ukraine, Latvia, Lithuania and Norway), while in 5 countries (Portugal, Denmark, Finland, Ireland, Sweden) no significant changes were seen. Frequency of DBC among adolescents in European countries and North America showed a more uniform pattern in 2010 as compared to patterns in 2002. DBC increased significantly in only six out of 19 countries from 2002 to 2010. There is need for continued education and campaigns to motivate adolescents to consume DBC. Comparing patterns across HBSC countries can make an important contribution to understanding regional /global trends and to monitoring strategies and development of health promotion programs.